Spatio Temporal Evaluation of Vegetation Cover in Sargodha (Pakistan) for Sustainable Urban Future - Riaz, Omar; Munawar, Huma; Khalid, Maryam (European Journal of Sustainable Development, 2017)
The monitoring of global vegetation through SRS (satellite remote sensing) data is central part of sustainable urban development and regional planning which is handy to improve our knowledge regarding spatial and temporal patterns and traits of vegetation in any area. In recent years rapid urbanization has converted Sargodha into 5th largest city of the Punjab which resulted in change and modification of urban morphology and invited the attention of researchers to investigate, analyze and evaluate the type, length and conditions of plant life. In this work an attempt was made to examine spatio temporal dynamics of vegetation cover in Sargodha by integration with multi temporal satellite images and GIS. The research shows the applicability of Landsat images for the evaluation of vegetation exchange between the years of 1992-2015. The findings of the study indicated that during the past 24 years, a dramatic change took place in reduction of greenness because of rapid increase in population distribution and density, urban development and other infrastructural development. The results highlighted the importance of NDVI for better effects concerning accuracy to evaluate the vegetation cover. Keywords: Urban expansion, Image processing, Vegetation cover, NDVI, Change Detection